2023
DOI: 10.1158/2159-8290.c.6549586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from Coordinated Transcriptional and Catabolic Programs Support Iron-Dependent Adaptation to RAS–MAPK Pathway Inhibition in Pancreatic Cancer

Abstract: <div>Abstract<p>The mechanisms underlying metabolic adaptation of pancreatic ductal adenocarcinoma (PDA) cells to pharmacologic inhibition of RAS–MAPK signaling are largely unknown. Using transcriptome and chromatin immunoprecipitation profiling of PDA cells treated with the MEK inhibitor (MEKi) trametinib, we identify transcriptional antagonism between c-MYC and the master transcription factors for lysosome gene expression, the MiT/TFE proteins. Under baseline conditions, c-MYC and MiT/TFE factors… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nuclear Receptor Coactivator 4 (NCOA4) is a crucial effector of ferritinophagy, a selective form of autophagy that targets ferritin to the autophagosome for degradation, allowing the release of iron that can be used for cellular processes (10). Interestingly, recent studies found that inhibition of NCOA4 results in delayed tumor growth and prolonged survival in murine models of pancreatic cancer, while enhanced ferritinophagy accelerates tumorigenesis (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear Receptor Coactivator 4 (NCOA4) is a crucial effector of ferritinophagy, a selective form of autophagy that targets ferritin to the autophagosome for degradation, allowing the release of iron that can be used for cellular processes (10). Interestingly, recent studies found that inhibition of NCOA4 results in delayed tumor growth and prolonged survival in murine models of pancreatic cancer, while enhanced ferritinophagy accelerates tumorigenesis (11,12).…”
Section: Introductionmentioning
confidence: 99%